Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 71242 by TawaTawa last updated on 13/Oct/19

Given:   (a/b) + (c/d)  =  (b/a) + (d/c)  Show that,           (a^2 /b^2 ) − (c^2 /d^2 )  =  (b^2 /a^2 ) − (d^2 /c^2 )

Given:ab+cd=ba+dcShowthat,a2b2c2d2=b2a2d2c2

Answered by MJS last updated on 13/Oct/19

α+β=(1/α)+(1/β)  ⇒ β=−α ∨ β=(1/α)  α^2 −β^2 =(1/α^2 )−(1/β^2 )  { ((β=−α ⇒ true for α≠0)),((β=(1/α) ⇒ true only for α=±1)) :}  ⇒ question wrong? α^2 −β^2 =(1/β^2 )−(1/α^2 ) is always  true for α≠0∧(β=−α∨β=(1/α))

α+β=1α+1ββ=αβ=1αα2β2=1α21β2{β=αtrueforα0β=1αtrueonlyforα=±1questionwrong?α2β2=1β21α2isalwaystrueforα0(β=αβ=1α)

Commented by $@ty@m123 last updated on 13/Oct/19

Thanks for this new(for me) concept.  But then where is the mistake  in my soution.  I am repeatedly cheking  but failed to find.

Thanksforthisnew(forme)concept.Butthenwhereisthemistakeinmysoution.Iamrepeatedlychekingbutfailedtofind.

Commented by MJS last updated on 13/Oct/19

you have made no mistake and your solution  is the same as mine: the question is “wrong”

youhavemadenomistakeandyoursolutionisthesameasmine:thequestioniswrong

Commented by TawaTawa last updated on 14/Oct/19

God bless you sir

Godblessyousir

Answered by JDamian last updated on 13/Oct/19

if   c   turns into   −c,  then  (a/b) − (c/d)  =  (b/a) − (d/c)    ((a/b) + (c/d))×((a/b) − (c/d))  =  ((b/a) + (d/c))  ×  ((b/a) − (d/c))    (a^2 /b^2 ) − (c^2 /d^2 )  =  (b^2 /a^2 ) − (d^2 /c^2 )

ifcturnsintoc,thenabcd=badc(ab+cd)×(abcd)=(ba+dc)×(badc)a2b2c2d2=b2a2d2c2

Commented by $@ty@m123 last updated on 13/Oct/19

I have a doubt on this process.  If it would be something like:  a+b=c  Would you still write  “if   c   turns into   −c,  then”

Ihaveadoubtonthisprocess.Ifitwouldbesomethinglike:a+b=cWouldyoustillwriteifcturnsintoc,then

Commented by TawaTawa last updated on 14/Oct/19

God bless you sir

Godblessyousir

Answered by $@ty@m123 last updated on 13/Oct/19

Solution:  Given:   (a/b) + (c/d)  =  (b/a) + (d/c)  ⇒((ad+bc)/(bd))=((bc+ad)/(ac))  ⇒bd=ac .....(1)  Now,  LHS= (a^2 /b^2 ) − (c^2 /d^2 )  =((a^2 d^2 −b^2 c^2 )/(b^2 d^2 ))  =((a^2 d^2 −b^2 c^2 )/(a^2 c^2 ))  =(d^2 /c^2 )−(b^2 /a^2 )  =RHS  pl. check your question.

Solution:Given:ab+cd=ba+dcad+bcbd=bc+adacbd=ac.....(1)Now,LHS=a2b2c2d2=a2d2b2c2b2d2=a2d2b2c2a2c2=d2c2b2a2=RHSpl.checkyourquestion.

Commented by TawaTawa last updated on 14/Oct/19

God bless you sir

Godblessyousir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com